Role of dermoscopy in the assessment of difficult to diagnose cases of pigmentary dermatoses: study from a tertiary care hospital - Yasmeen J Bhat; Faizan Y Shah; Insha Latif; Najm-u Saqib; Aaqib A Shah; Yaqzata Bashir; Rita Devi; Uzair K Dar; Masarat Naushad; Iffat Hassan; Kewal Krishan (Wolters Kluwer Medknow Publications, 2022)
Background: Pigmentary disorders are a common skin affliction causing great distress and anguish among those affected. Dermoscopy is a noninvasive diagnostic modality which has great potential in the diagnosis of these disorders. Objectives: To assess the dermoscopic features relevant to the diagnosis of pigmentary dermatoses in patients presenting to our tertiary care hospital. Methods: This was a cross-sectional study conducted in patients presenting to pigmentary dermatoses clinic of our hospital over a period of 1 year. A comprehensive evaluation with special emphasis on dermoscopy was performed in all patients. The dermoscope used was DL3N Dermlite (10X). Additional investigations were carried out as deemed necessary to clinch a final diagnosis. Results: The study included a total of 200 cases with 90 males and 110 females, with age ranging from 6 months to 69 years and a mean age of 24.43 ± 17.07 years. The pigmentary dermatoses encountered were divided into three groups − disorders of hypopigmentation, facial melanoses, and other pigmentary disorders. Dermoscopic findings most relevant to diagnosis were compiled and tabulated. Conclusion: Dermoscopy played a significant role to rule out ominous diagnosis with accuracy comparable to histopathology, when carried out by an expert. The need for an invasive procedure such as skin biopsy was evaded in a number of cases.